AGROTOURISM AS THE ECONOMICS TRANSFORMATION OF THE TOURISM VILLAGE IN BALI (CASE STUDY: BLIMBINGSARI VILLAGE, JEMBRANA, BALI) - I Wayan Ruspendi Junaedi; I Gusti Bagus Rai Utama (Journal of Business on Hospitality and Tourism, 2016)
In this research is focused on tourist behavior and the local communities on the demand   of agro tourism   development.   The study   is aimed   at formulating the best model to develop agro tourism in Bali. The model tourist attraction is expected by the rating is community activities, plantation area, and village's uniqueness. On the amenities, the tourist expect amenities which include, among others: local accommodations, tracking area, places to gain knowledge and experience, places to rest and relax, escape area, places to meet people and interaction,  places to escape the daily routine, learning experiences, and  new places. On the accessibility, the tourists rate that the distance of the village of Blimbingsari as the barriers factor, and difficult to reach by public transport. In addition to a considerable distance, the path that must be passed to the Village Blimbingsari also includes the busy lanes and frequent traffic jams. The results of the research that has been done indicates that Blimbingsari tourism village been managed well which is evident from their local community involvement as tourism committee, guide services or travel agents link, local guide services that handling by tourism committee, and government support by Regent licensee.